Transforming Negative Thoughts into Self-Confidence: The Impact of Cognitive Restructuring on Adolescents - Takdir, Annisya Muthmainnah; Darusman, Mhd. Ricky; Devi, Dini Fidyanti (Journal of Psychological Perspective, 2025)
Adolescents often struggle with low self-confidence, exacerbated by negative thought patterns and irrational beliefs that hinder their social and emotional development. This study explores the effectiveness of cognitive restructuring, a core component of cognitive-behavioral therapy (CBT), in enhancing self-confidence among adolescents. The intervention focused on identifying, challenging, and replacing negative thoughts with constructive alternatives. A single-subject case study design was employed, with pretest and posttest measures on the Self-Confidence Scale to assess changes. Results indicated a significant increase in self-confidence scores, from 72 (low confidence) to 97 (moderate confidence). Qualitative data revealed behavioral improvements, such as reduced hesitation in social interactions and increased willingness to express opinions. The subject's belief in irrational thoughts, like fearing social judgment, was reduced, demonstrating cognitive restructuring’s role in shifting negative perceptions. This study highlights the transformative potential of cognitive counseling in fostering adolescent self-confidence. By addressing irrational beliefs and encouraging adaptive thinking, cognitive restructuring not only improved the subject’s self-esteem but also promoted positive social behavior. These findings align with existing literature, emphasizing the value of CBT-based interventions in promoting mental well-being. The study underscores the importance of integrating cognitive restructuring techniques into educational and counseling programs to support adolescents facing self-confidence challenges. However, its single-case design limits generalizability, warranting further research with larger, diverse samples. This approach offers a promising pathway for practitioners to help adolescents develop resilience and a healthier self-concept.